Implementation of Local Wisdom of Sidomukti Batik in Development Creative and Sustainable Products in Surakarta - Latif, B Syarifuddin; Ramli, Muhamad; Demilingo, Ramang H; Raflikeza, Muhammad Firdaus (CV ODIS, 2024)
Community service programs are important as part of the Tridharma of higher education in introducing local wisdom in the community. This service activity aims to introduce the local wisdom of Sidomukti Batik in Surakarta. The method for implementing community service activities is through mentoring in the form of theory and practice. The target of the activity is creative economy actors who want to learn about the local wisdom of Sidomukti Batik. Place of activity at the Tourism and Creative Economy Department, Surakarta City Hall. Introductory activities through mentoring local wisdom to creative economy actors are given the theory of developing creative Batik Sidomukti products by involving parents who are experts in this field. This community service proposal was planned to apply local wisdom from Batik Sidomukti as a central element in efforts to develop creative and sustainable products in Surakarta. In this effort, we intend to investigate the complex problems faced by batik businesses, local craftsmen, and artist communities when facing the dynamics of globalization and the struggle to maintain the authenticity of local cultural values. Among the problems identified, there is a decline in the competitiveness of local batik products in the global market, the risk of losing the traditional skills of craftsmen, and a shift in consumer preferences towards tradition-based products. In facing these challenges, this activity's main objective includes formulating innovative and sustainable solutions and re-weaving local cultural identity which is increasingly fading. The design of this activity includes several stages involving the identification of local wisdom from Sidomukti Batik, active participation of business actors, craftsmen, and artist communities in the product development process, and the implementation of training programs to ensure the sustainability of traditional skills. We are also considering holding exhibitions and product promotion strategies to increase exposure to Sidomukti batik locally and globally. This research will be carried out collaboratively, involving related parties such as batik business actors, local craftsmen, artist communities, and local government.